Amphetamine in postmortem liver sample? - Davorka Sutlovic; Maja Versic Bratincevic; Marija Defi nis- Gojanovic (Forensic Science Today - Peertechz Publications, 2017)
The aim of this paper is to present the formation of false positive amphetamine in postmortem liver samples and to determine conditions that are responsible for its formation.  Postmortem samples used in the experiment underwent toxicological analysis and all liver samples gave positive results for amphetamine. There was no evidence that patients consumed amphetamine or any other substance that could have produced such fi nding. We tested liver tissue for better understanding of false positive amphetamine. The infl uence of different temperatures in different time periods was studied on liver samples, which were divided into several pieces with identical weight. Samples were qualitatively and quantitatively determined and analyzed using gas chromatography-mass spectrometry technique (GC/ MS).  Liver samples gave false positive results for amphetamine after ten days at the 32.5 0C. After derivatization, the results on amphetamine have not been positive. Toxicological fi nding for a presence of a positive amphetamine in liver sample is not suffi cient and should be confi rmed on other biological samples. Also, there is a need for derivatization of biological samples to confi rm and eliminate the suspicion of false positive fi ndings.